Audiovisual Approaches To Prevent Bullying Behavior In Schools - Kurniastuti, Devi Fahwi; Valentina, Ratna Wulan; Pratama, Risky Eka; Agista, Yessa Ayu; Santoso, Aris Prio Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Bullying is a serious social problem in Indonesia, especially among children and adolescents. According to data from the Ministry of Women Empowerment and Child Protection, in 2023, there were 20,000 cases of bullying reported to the authorities. These bullying cases can hinder children from learning in school, and have a negative impact on the physical and psychological development of the victims. This study aims to understand the definition, impact, types, and ways to prevent bullying. This study uses a literature study method by collecting data from various sources, such as books, journal articles, and previous research results. The results of the study show that audiovisual methods are very focused on the senses of hearing and vision, so they can effectively utilize the child's sensory abilities, namely brain stimulation that can change behavior.